Perancangan Superstructure Jembatan Kereta Api Bentang 100 Meter Tipe Rangka Baja - Erlangga, Aditya Wahyu; Atmaja, Dadang Sanjaya; Dewi, Puspita (Politeknik Perkeretaapian Indonesia Madiun, 2017)
This study discusses long bridge superstructure planning. The reference used for the design of the bridge is the Regulation of the Minister of Transportation No. 60 of 2012 on Technical Requirements of Railways, AREMA and the rules of the European Union. The loading of the superstructure of the railway bridge includes dead load, live load, shock load, horizontal load, and wind load. This bridge profile needs analysis using the influence line method with SAP 2000 application. The result of superstructure analysis of 100 meter railway bridge type of lower truss frame shows that the size for structure profile, stringer, and cross girder must be specially designed by utilizing SM400 type steel plate with welding. From the analysis result, the working force of stringer is 1618,74 kN with a deflection of 11,58 mm; Force on a transverse girder of 2348.16 kN; Upperchord of 6340.45 kN; Lower Frame (Lowerchord) of 7441.33 kN; And members in the amount of 5599.48 kN. Of the styles are designed profiles as follows: 1 UFLG 105 x 2.5; 2WEB 80 x 2.5; 1 UFLG 80 x 2.5 for lowerchord, 1 UFLG 105 x 3.6; 2WEB 80 x 2.5; 1 UFLG 80 x 3.6 for upperchord and WF 72X x 80 x 2 x 2 For diagonal member.